Are there Social Limits to Growth? - Kjell Arne Brekke; Richard B. Howarth; Karine Nyborg (Statistics Norway, Research Department, 1998)
Hirsch (1976) suggested that as consumption grows, an increasing proportion of the benefits people derive from consumption is due to a status effect. Status is a relative concept that cannot be increased on average; thus it may seem reasonable to expect that as consumption grows, the marginal benefits of consumption decrease more than the marginal benefits of status. In equilibrium, however, there will be price effects that may more than outweigh this effect. Thus, there is no a priori reason to expect more status-seeking behavior in richer societies.
Keywords: D11; D50; 330; Status-seeking; relative consumption